TINJAUAN HUKUM TENTANG PENGGUNAAN LOGO PERUSAHAAN YANG DI AMBIL DARI INTERNET TANPA IZIN UNTUK TUJUAN KOMERSIAL BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK - Alfia Azka (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACLegal aspect that protects human rights in intellectual property is the Intellectual Property Rights Law (IPR). The existence of Intellectual Property Rights basically has economic value. Therefore it is not excessive if the results of human intellectual work are given adequate legal protection.This type of research in legal research is normative juridical research. The normative juridical research method is the method or method used in legal research conducted by examining existing library materials.The formulation of the issues that will be discussed are: (1) How is the legal protection of the rights holders of the Rolling Stones band logo that are used without rights by clothing or t-shirt manufacturers in Indonesia? (2) What are the legal consequences for clothing or t-shirt manufacturers who produce the Rolling Stones band logo without rights? and (3) What is the way to settle if there is a dispute between the rights holders of the Rolling Stones band logo and the producers of clothing or T-shirts without rights?Based on the results of the study concluded that, legal protection of the work of the band logo is something that needs special attention because nowadays more and more t-shirt manufacturers do not have the right or permission but can duplicate the copyright to obtain as much material as possible. The legal protection is in the form of preventive preventive legal protection and repressive legal protection in the form of law enforcement against brand violations, as stipulated in Law No. 15 of 2001 concerning Trademarks.